Pengembangan Media Web Google Sites pada Keterampilan Membaca Pemahaman Bahasa Inggris Kelas IV SDN Tajungan Bangkalan - Nadhea Fatiha; Humairah Fauziah (Mataram University, 2026)
The purpose of this development research was to develop a Google Sites web-based learning media for English reading comprehension skills for fourth-grade students at SDN Tajungan Bangkalan that is valid, effective, and attractive. This study employed the 4D development model consisting of four stages: Define, Design, Development, and Disseminate. The subjects of this research were fourth-grade students of SDN Tajungan Bangkalan. The validation results showed that the instructional design expert assessment obtained a percentage of 99%, categorized as very valid. The learning material expert assessment obtained a percentage of 76%, categorized as valid, and the learning media expert assessment obtained a percentage of 92%, categorized as very valid. The effectiveness of the media was demonstrated by the average teacher activity score of 92%, categorized as very effective, and the average student activity score of 98%, categorized as very effective. In addition, student learning outcomes analyzed using the classical learning mastery formula showed a mastery level of 100%. The attractiveness of the media was indicated by the teacher response questionnaire, which obtained a percentage of 100%, categorized as very attractive, and the student response questionnaire, which obtained a percentage of 99%, categorized as very attractive.